Sub-chronic stress exerts partially distinct behavioral and epigenetic effects in male and female mice - Domanico, Matthew J.; Stevens, Sophie; Wainston, Iris; Khoo, Emily; McCall, Corey; Swack, Benjamin D.; Sachs, Benjamin D. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionStress-related disorders, such as major depression, anxiety disorders, and post-traumatic stress disorder, lead to considerable disease burden and are notoriously difficult to treat. These disorders are characterized by striking sex differences, but the neurobiological underpinnings of the disparities in mental health between men and women remain largely undefined. With an improved understanding of the biological factors that promote or protect against psychopathology, it may become possible to design interventions that enhance resilience. Preclinical research using rodent models can provide fundamental insight into potential sex differences in the neurobiological consequences of stress, which could have important implications for our understanding of stress-related disorders.MethodsTowards this end, the current work compared stress-induced alterations in DNA methylation and behavior in male and female c57BL/6 mice. A subchronic stress paradigm consisting of five days of mild stressors was used, and behavioral outcomes were assessed using the elevated plus maze and the light-dark emergence, open field, forced swim and effort-related reward choice tests.ResultsStatistical analyses using two-way ANOVAs revealed that although some of the effects of stress in the light-dark emergence test were specific to females, both sexes were susceptible to several behavioral consequences of this stress paradigm. Stress was also shown to decrease global DNA methylation in the nucleus accumbens one week following the end of stress exposure in both sexes, but no significant effects were observed two hours following stress. In the hippocampus, no global DNA methylation differences were observed at either time point. Targeted evaluations using methylation-specific PCR revealed sex differences in stress-induced changes in DNA methylation at sites in the prodynorphin and inhibitory kappa B kinase beta genes in the nucleus accumbens. In contrast, no significant sex-by-stress interactions were observed for methylation changes in the hippocampus, although stress significantly increased DNA methylation of prodynorphin and inhibitory kappa B kinase beta two hours after the final stress exposure and reduced methylation of the NEMO and D2 dopamine receptor genes one week following stress.DiscussionOverall, these findings provide further evidence of sex differences in stress susceptibility and suggest that sex differences in epigenetic adaptations to stress could contribute to the partially distinct behavioral outcomes of stress in males and females.